2021
DOI: 10.1021/jacsau.1c00217
|View full text |Cite
|
Sign up to set email alerts
|

Role of Fe Species of Ni-Based Catalysts for Efficient Low-Temperature Ethanol Steam Reforming

Abstract: The suppression of methane and coke formation over Ni-based catalysts for low temperature ethanol steam reforming remains challenging. This paper describes the structural evolution of Fe-modified Ni/MgAl 2 O 4 catalysts and the influence of iron species on methane and coke suppression for low temperature ethanol steam reforming. Ni–Fe alloy catalysts are gradually oxidized by water to generate Ni-rich alloy and γ-Fe 2 O 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 78 publications
0
27
0
Order By: Relevance
“…Recently, a new scheme from non‐active metal modification Ni‐base catalysts and constructed bimetallic tactics have been attested to be effective on degrading coke deposition and ameliorating catalytic selectivity [297–303] . Wu et al [297] . describes the structural evolution of Fe‐modified Ni/MgAl 2 O 4 catalysts for ESR, and found that the electron transfers from Fe to Ni in Ni−Fe alloy weakens the CO adsorption and effectively reduces the CO/CO 2 methanation (Figure 12).…”
Section: Bimetallic Catalysis Interaction For Esrmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, a new scheme from non‐active metal modification Ni‐base catalysts and constructed bimetallic tactics have been attested to be effective on degrading coke deposition and ameliorating catalytic selectivity [297–303] . Wu et al [297] . describes the structural evolution of Fe‐modified Ni/MgAl 2 O 4 catalysts for ESR, and found that the electron transfers from Fe to Ni in Ni−Fe alloy weakens the CO adsorption and effectively reduces the CO/CO 2 methanation (Figure 12).…”
Section: Bimetallic Catalysis Interaction For Esrmentioning
confidence: 99%
“…Recently, a new scheme from non-active metal modification Ni-base catalysts and constructed bimetallic tactics have been attested to be effective on degrading coke deposition and ameliorating catalytic selectivity. [297][298][299][300][301][302][303] Wu et al [297] describes the structural evolution of Fe-modified Ni/ MgAl 2 O 4 catalysts for ESR, and found that the electron transfers from Fe to Ni in NiÀ Fe alloy weakens the CO adsorption and effectively reduces the CO/CO 2 methanation (Figure 12). In addition, the γ-Fe 2 O 3 species with oxidizing ability also promotes the transformation of ethoxy to acetate groups, avoiding CH 4 formation and promoting the elimination of carbon deposits.…”
Section: Nià M (M = Sn W Mo Fe) Bimetallic Catalystsmentioning
confidence: 99%
See 3 more Smart Citations